Scutellariae Radix and Atractylodis Macrocephalae Rhizoma pairs ameliorate preeclampsia via PI3K/AKT/eNOS pathway - Sun, Shujun; Li, Jie; Qin, Dingmei; Yang, Xiaoxiao; Zhang, Huilin; Yang, Yue; Li, Mengmeng; Jin, Ruihua; Dai, Jianye; Liu, Yong (Frontiers in Pharmacology, 2025)
IntroductionPreeclampsia stands as a leading cause of maternal mortality. Scutellariae Radix and Atractylodis Macrocephalae Rhizoma (SA) is a commonly employed traditional Chinese medicine pair in the treatment of preeclampsia, yet the underlying mechanisms of their protective effects against preeclampsia remain elusive.MethodsIn this study, the N- nitro-L-arginine methyl ester (L-NAME) was utilized to establish a preeclamptic pregnant mouse model, and the protective effects of SA were systematically evaluated. A comprehensive approach integrating network pharmacology analysis, quantitative proteomics, and in vitro experiments was adopted to probe into the relevant mechanisms.ResultsIt was demonstrated that SA could significantly ameliorate the systolic blood pressure, urinary protein levels, and pathological damage in the kidneys and placenta of mice. Moreover, in vitro experiments further validated the promoting effects of SA, baicalin, and atractylenolide I on the proliferation and migration of HTR-8/SVneo cells. Baicalin and atractylenolide I are the main active and quality control components of SA. Network pharmacology analysis, quantitative proteomics and molecular docking revealed that the PI3K/Akt pathway is a potential mechanism through which SA alleviates preeclampsia. Further investigations showed that SA could reverse L-NAME-induced inhibition of the PI3K/p-Akt/Akt signaling pathway, upregulating eNOS expression and ultimately alleviating vasoconstriction and other preeclampsia-related symptoms.ConclusionSA has the capacity to improve preeclampsia-induced increases in blood pressure and urinary protein, holding promise as a novel strategy for the treatment of preeclampsia.